Structure and Tropomyosin Binding Properties of the N-Terminal Capping Domain of Tropomodulin 1 - Greenfield, Norma J. (The Biophysical Society, 2005)
Two families of actin regulatory proteins are the tropomodulins and tropomyosins. Tropomodulin binds to tropomyosin (TM) and to the pointed end of actin filaments and “caps” the pointed end (i.e., inhibits its polymerization and depolymerization). Tropomodulin 1 has two distinct actin-capping regions: a folded C-terminal domain (residues 160–359), which does not bind to TM, and a conserved, N-terminal region, within residues 1–92 that binds TM and requires TM for capping activity. NMR and circular dichroism were used to determine the structure of a peptide containing residues 1–92 of tropomodulin (Tmod1(1-92)) and to define its TM binding site. Tmod1(1-92) is mainly disordered with only one helical region, residues 24–35. This helix forms part of the TM binding domain, residues 1–35, which become more ordered upon binding a peptide containing the N-terminus of an α-TM. Mutation of L27 to E or G in the Tmod helix reduces TM affinity. Residues 49–92 are required for capping but do not bind TM. Of these, residues 67–75 have the sequence of an amphipathic helix, but are not helical. Residues 55–62 and 76–92 display negative (1)H-(15)N heteronuclear Overhauser enhancements showing they are flexible. The conformational dynamics of these residues may be important for actin capping activity.